The Effect of Celebrity Endorser on Purchase Intention Cosmetic Product in Millennial Generation Consumers - Moh Farid Najib; Dara Yuri Andita; Rizki Zulfikar; Dewi Purnamasari (Journal of Marketing Innovation (JMI), 2021)
The use of celebrity endorsers has become even more attractive to many consumers, including cosmetic consumers in Indonesia. Using the appropriate celebrity endorser is believed as one way to increase sales and to reduce the budget for advertising that become issues for certain companies. The purpose of this study is to examine the factors of the source credibility model consist of attractiveness, trustworthiness, and expertise that have positive or significant effects on consumer purchases intention. Questionnaire were distributed to millennial generation as the targeted cosmetic consumers in Indonesia. By using Likert scale points, the results of the questionnaire distribution received a total of 475 respondents, but only 438 questionnaires used in the test. This study was tested by using SEM-PLS. The results showed that all variables had positive and significant influences on consumer purchase intention in Indonesia. This study examined the influence of celebrity endorsers on social media on the purchase intention of the millennial or Y generation as the focus. The next research is expected to carry the same model, but with different generation as the object of the study.